lmportance of surgery of the hand in modern medicine - Fossati, Enrique (Cirugía del Uruguay, 1985)
. Analysis of the importance of the hand-upper limb in human beings. The speciality Surgery of the Hand is defined: origins, significance, place in medicine nowadays in the light of recen! scientific advancement and its unlimited progression in fut